If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + 8 = 2(1 + 2x) Reorder the terms: 8 + 2x = 2(1 + 2x) 8 + 2x = (1 * 2 + 2x * 2) 8 + 2x = (2 + 4x) Solving 8 + 2x = 2 + 4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4x' to each side of the equation. 8 + 2x + -4x = 2 + 4x + -4x Combine like terms: 2x + -4x = -2x 8 + -2x = 2 + 4x + -4x Combine like terms: 4x + -4x = 0 8 + -2x = 2 + 0 8 + -2x = 2 Add '-8' to each side of the equation. 8 + -8 + -2x = 2 + -8 Combine like terms: 8 + -8 = 0 0 + -2x = 2 + -8 -2x = 2 + -8 Combine like terms: 2 + -8 = -6 -2x = -6 Divide each side by '-2'. x = 3 Simplifying x = 3
| 5n^2+38n-63=0 | | -7c+4-c=-2(c+3) | | -2x(x+5)=3x-15 | | 0x+8=20 | | 4x-10=-4x | | N^2/2n-1 | | 3(3x+4)=3x+18 | | 10a=3.5(17) | | 2x+58=3(2+5x) | | 8x-(4x+7)+11=2x | | 7v^2-2v=0 | | 2a+6-6a= | | -(6m+4)=4m-2(6m+2) | | 9a+3b+c=1750 | | -4k+2(5k-6)= | | 20n^2-16n-160=0 | | -4/.75 | | 81x^2-1/16 | | 5+6y-18y= | | 3y+2y-8=17 | | 4x+8=2(3+x)+2(x+1) | | (6x-10)(4x-9)= | | 2x^2+10x-85=0 | | x-6=9-4x | | 2n^2+25n+63=0 | | 14-(-8x)+4x-(-12)= | | 3(b+4)+b=-6(3+b) | | 7n^2+6n+42=0 | | 7x-(6x+8)=3x-46 | | 11+3x-7=6x-5-3x | | 2w+10=22 | | 2+3(2-5)-8=2(x-5) |